1997
DOI: 10.1016/s0092-8674(01)80012-x
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Xist RNA Mediates Initiation of X Chromosome Inactivation

Abstract: The onset of X inactivation is preceded by a marked increase in the level of Xist RNA. Here we demonstrate that increased stability of Xist RNA is the primary determinant of developmental up-regulation. Unstable transcript is produced by both alleles in XX ES cells and in XX embryos prior to the onset of random X inactivation. Following differentiation, transcription of unstable RNA from the active X chromosome allele continues for a period following stabilization and accumulation of transcript on the inactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
200
3
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(218 citation statements)
references
References 44 publications
14
200
3
1
Order By: Relevance
“…It was also proposed earlier that the modulation of Xist chromatin structure might play a role in how Tsix regulates Xist (Navarro et al 2005;Sado et al 2005). Interestingly, a recent study has suggested that up-regulation of Xist RNA observed on the future inactive X is not due to the increased stability of the Xist transcript as suggested earlier but is regulated by Tsix Sheardown et al 1997;Sun et al 2006). Lee and colleagues (Sun et al 2006) reported that Tsix downregulation on the future inactive X induces a transient heterochromatic state to Xist, followed by high levels of Xist expression.…”
Section: XCImentioning
confidence: 60%
“…It was also proposed earlier that the modulation of Xist chromatin structure might play a role in how Tsix regulates Xist (Navarro et al 2005;Sado et al 2005). Interestingly, a recent study has suggested that up-regulation of Xist RNA observed on the future inactive X is not due to the increased stability of the Xist transcript as suggested earlier but is regulated by Tsix Sheardown et al 1997;Sun et al 2006). Lee and colleagues (Sun et al 2006) reported that Tsix downregulation on the future inactive X induces a transient heterochromatic state to Xist, followed by high levels of Xist expression.…”
Section: XCImentioning
confidence: 60%
“…However, experiments that would conclusively test the postulated roles for the vast majority of eukaryotic long ncRNAs have not yet been performed (5). Careful interrogation of specific loci is necessary to distinguish between ncRNAs that represent mere transcriptional ''noise'' and those that have a bona fide role in regulation and development (17)(18)(19)(20)(21)(22). Long intergenic ncRNAs also exist in yeast, and despite the tractability of this model system, most remain uncharacterized.…”
mentioning
confidence: 99%
“…A recent study shows that the lncRNA XIST, responsible for X-chromosome inactivation in female mammalian cells, also plays a role in the chromatin organization of the inactive X chromosome (Xi) [98]. XIST is a 17-kb long lncRNA transcribed from the X chromosome, which recruits PRC2 for suppression [99]. Further investigations identified several additional proteins that interact with XIST such as the ATRX RNA helicase, YY1 and hnRNPU [97,100,101].…”
Section: Non-coding Rnas As Modulators Of Chromatin State and Organizmentioning
confidence: 99%